Development, validation and testing of a skin sampling method for assessment of metal exposure - Erfani, Behnaz; Midander, Klara; Lidén, Carola; Julander, Anneli (Contact dermatitis, 2017)
Summary Background Nickel, cobalt and chromium are frequent skin sensitizers. Skin exposure results in eczema in sensitized individuals, the risk being related to the skin dose. Objectives To develop a self‐sampling method for quantification of skin exposure to metals, to validate the method, and to assess its feasibility. Methods Defined metal doses (0.01–5 µg) were applied to the fingers of 5 participants. Skin areas (2 cm2) were sampled with 1% HNO3, either as 0.1 ml on a swab, or as 0.5 ml on a wipe. Furthermore, 17 participants performed self‐sampling by swab after 2 h of leisure activity. Samples were extracted in 1% HNO3 and analysed by inductively coupled plasma mass spectrometry. Results The sampling efficiency by swab was 46%, as compared with 93% for acid wipe sampling, for all tested doses. Most metal from the skin dose was detected in the first swab (33–43%). Despite lower sampling efficiency by swab, skin doses of metals following 2 h of leisure activity without hand washing were quantified in all participants, and ranged from 0.0016 to 0.15 µg/cm2, from 0.00014 to −0.0020 µg/cm2 and from 0.00048 to −0.027 µg/cm2 for nickel, cobalt, and chromium, respectively. Conclusions The results indicate a future potential of skin sampling by swab to detect and monitor metals on skin by self‐sampling. This will contribute to better knowledge of metal skin exposure among dermatitis patients, workers, and the general population.